2023
DOI: 10.3389/fgwh.2023.1009473
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the private and professional lives of highly educated women working in global health in Europe—A qualitative study

Abstract: BackgroundThe COVID-19 pandemic has led to a deepening of existing inequalities and a rollback of achievements made in gender equality. Women in Global Health (WGH) is a global movement that aims to achieve gender equality in health and increase female leadership in global health. Here, the aim was to understand how the pandemic affects the private and professional lives of women working in global health in different European countries. Suggestions for future pandemic preparedness including how gender perspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…In the meantime, the women who work from home during the lockdown go through moderately increased physical and mental load (7). Because some women worked in sectors that had suffered a lot, like tourism, healthcare, and the service industry, they were more vulnerable to lose their jobs (8). A study showed that COVID-19 impacted working women, making it more difficult for them to maintain a healthy work/life balance, causing a significant setback in their long quest for equality in the workplace (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, the women who work from home during the lockdown go through moderately increased physical and mental load (7). Because some women worked in sectors that had suffered a lot, like tourism, healthcare, and the service industry, they were more vulnerable to lose their jobs (8). A study showed that COVID-19 impacted working women, making it more difficult for them to maintain a healthy work/life balance, causing a significant setback in their long quest for equality in the workplace (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Because some women worked in sectors that had suffered a lot, like tourism, healthcare, and the service industry, they were more vulnerable to lose their jobs (8). A study showed that COVID-19 impacted working women, making it more difficult for them to maintain a healthy work/life balance, causing a significant setback in their long quest for equality in the workplace (8)(9)(10). Iranian researchers have also shown that COVID-19 influenced social, familial, professional, and financial issues, psychological reactions, access to services, leisure time, and physical problems of Iranian women (11).…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Individuals with higher education levels also reported higher incidences of these mental health issues, possibly due to information overload and heightened concern about the pandemic's risks. [30][31][32] Previous studies have shown that insomnia prevalence generally increases with age, but a study during the pandemic in France found higher rates of insomnia among young people, attributed to increased social isolation and economic difficulties. 33,34 Additionally, chronic diseases like hypertension, diabetes, and mental disorders are closely linked to poorer mental health outcomes, underscoring the importance of holistic management of both physical and mental health in these patients.…”
mentioning
confidence: 99%